LABOR INCLUSION OF PEACE SIGNER IN BPO COMPANIES: A CONTRIBUTION OF SOCIAL MARKETING - León Guatame, Aida Ximena (2024)
Exploratory research, with a quantitative approach and a correlational scope, aims to identify influencing factors of the stigmatization or labor inclusion of peace signer persons by companies in the BPO sector in Bogota, from analyzing the variables of the social learning model and reciprocal determinism; in order to provide elements to propose Social Marketing actions that increase the hiring of peace signer people. The findings show that the persons in charge of hire in the companies of the Business Process Outsourcing (BPO), agree with the inclusion of peace signer persons in the job market. This study provides useful elements for Social Marketing with the aim of facilitate their inclusion in the job market.